Stunting in Children Aged 0-5 Years: A Literature Review on Prevention and Control Strategies - Meilin Anggreyni; Ince Rahmi; Rizka Rizka; Sudirman Sudirman; Ahmad Yani; Finta Amalinda (Pancasakti Journal Of Public Health Science And Research, 2025)
Stunting is a significant public health issue affecting children under five years old, leading to long-term consequences on growth and development. The method used in this study is Systematic Literature Review (SLR). Research conducted systematically by following the rules with the flow of literature review to avoid subjective misunderstandings from researchers. The data used in the study are sourced from national and international scientific publication databases such as PubMed, Google Scholar and Science Direct. The search keywords for the article are arranged based on the PICOS Framework, the keywords are "stunting in children 0-5 years", "stunting prevention" and "stunting control strategy". The review identified the effective interventions highlighted include promoting exclusive breastfeeding, improving maternal nutrition, and implementing community-based nutrition programs. Additionally, the role of education and awareness in fostering healthy dietary practices among families was emphasized. The results of the review conducted on 3 national journal articles and 11 international journal articles indicate that strategies for the prevention and control of stunting must include a holistic approach that involves health promotion, nutritional improvement, sanitation enhancement, community empowerment, and the increase of parental self-efficacy. It is hoped that the prevalence of stunting in Indonesia will continue to decline, thereby improving the quality of future human resources to realize a competitive Golden Generation of Indonesia.